Get rid of parentheses first.
-12÷3•(-8+16-6)+2 =
-12÷3•(2)+2 = ?
Simplify this expression.
-12÷3•(-8+(-4^2)-6)+2.
I'm confused on how to solve this. Thank you for the help.
20 answers
so first I s implifyed 4/1 which is (4 * x) * -22) + 2 the I Pulled out like terms 3.1 then I pulled out like factors 2 - 88x= -2 * (44x - 1) and then I got -2 * (44x - 1)
its late but here :D hope i helped out you
its late but here :D hope i helped out you
wait no its -6 my teacher says so now there lol
PEMDAS
did u ever get it
4 years later and still nobody knows how
Four years ago and nobody knows smhhhh
5 yars and kno whan knows
and only 120 views on this question per year, intresting
and only 120 views on this question per year, intresting
Adriel Jorge:
Expression- -12÷3*(-8+(-4)^2-6)+2
First to simplify this expression I need to use the order of operation PEMDAS. So the parentheses would be worked with first. And in the parentheses I also need to do PEMDAS. So i would do the E in PEMDAS which is Exponents.
-12÷3*(-8+(-4)^2-6)+2=
-12÷3*(-8+(-8)-6)+2
Next I still need to do the parenthesis, so the next thing using PEMDAS is the A which is add.
-12÷3*(-8+(-8)-6)+2=
-12÷3*(-16-6)+2
Then third i still need to do what's left in the parentheses which is subtracting.
-12÷3*(-16-6)+2=
-12÷3*(-16-6)+2
-12÷3*-22+2
Fourth know that i have done everything that is in the parenthesis, so again using PEMDAS i would multiple.
-12÷3*-22+2=
-12÷(-19)+2
Next again using PEMDAS i would use and the next thing would be dividing the numbers.
-12÷(-19)+2=
-31+2
Lastly all that would be needed to do to fully simplify this expression is to add.
-31+2=
=-29 so i finally fully simplified the expression
Expression- -12÷3*(-8+(-4)^2-6)+2
First to simplify this expression I need to use the order of operation PEMDAS. So the parentheses would be worked with first. And in the parentheses I also need to do PEMDAS. So i would do the E in PEMDAS which is Exponents.
-12÷3*(-8+(-4)^2-6)+2=
-12÷3*(-8+(-8)-6)+2
Next I still need to do the parenthesis, so the next thing using PEMDAS is the A which is add.
-12÷3*(-8+(-8)-6)+2=
-12÷3*(-16-6)+2
Then third i still need to do what's left in the parentheses which is subtracting.
-12÷3*(-16-6)+2=
-12÷3*(-16-6)+2
-12÷3*-22+2
Fourth know that i have done everything that is in the parenthesis, so again using PEMDAS i would multiple.
-12÷3*-22+2=
-12÷(-19)+2
Next again using PEMDAS i would use and the next thing would be dividing the numbers.
-12÷(-19)+2=
-31+2
Lastly all that would be needed to do to fully simplify this expression is to add.
-31+2=
=-29 so i finally fully simplified the expression
uh, no meme. I need the answers.
6 years later
HEEEEEELP
6 years
YEARS MATE YEARS THIS IS SAD
Literally 7 years later. These people are either done with college or in it lmaooaoaooaoaoaoooaoaoaooaoaoaoaoaoaoaoaoaoaoaooaoaoaoaoaoaoaozaoaoaoaoaoaoaooaoaoaoaoaoaoaoaoaoaooaoaoaoaoaoaaooaoaaooaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaoaooaoaoaoaoaoaoaoaooaoaoaoaoaoaoaooaoaoaoaoaoaoaooaoaoaoaoaoaooaoaoo
bruhhhh
12 / 3 · (-8+(-4)²-6+2)=
You start with (-4)² Which=16
- 12/3·(-8+16-6+2)=4
-12/3·4=
Now we have 3·4 which=12
-12/12=-1
Make sure to divide when checking my answer.
100% Correct
You start with (-4)² Which=16
- 12/3·(-8+16-6+2)=4
-12/3·4=
Now we have 3·4 which=12
-12/12=-1
Make sure to divide when checking my answer.
100% Correct
7 years I'm guessing now?
bruh did jeff give the answer lol
why